Successful management of belimumab after obinutuzumab in a patient with systemic lupus erythematosus: a case report with an 18-month follow-up - Pu, Xiuxiu; Ye, Qiao; Zhu, Lin; Yan, Tingting (Frontiers in Immunology, 2024)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease, and despite the availability of multiple treatments, striking a balance between long-term efficacy and side effects remains a major clinical challenge. B-cell-directed therapy has attracted much attention because of its unique mechanism of action. Belimumab and obinutuzumab, as representative drugs for B-cell-directed therapy, have shown their respective advantages for SLE treatment. However, data on combination therapy with obinutuzumab and belimumab are currently unavailable.We present the severe case report of a patient who was diagnosed with lupus nephritis (LN) with gastrointestinal involvement and developed acute renal failure. The patient responded to the first dose of obinutuzumab but failed to achieve a complete response to LN. The repeated use of obinutuzumab was limited by persistently low IgG levels and frequent infections. This is a real-world challenge that must be addressed. Therefore, the patient was subsequently treated with a novel sequential regimen of obinutuzumab followed by belimumab. After 18 months of follow-up, the patient achieved a complete clinical response with a favourable safety profile, along with the conversion of all autoantibodies from positive to negative and sustained negativity. To date, the patient has achieved a dual clinical and serological response.There is reason to believe that this novel combination regimen could be developed as a therapeutic strategy, with the expectation of balancing efficacy and safety.